MYB transcriptionally regulates the miR-155 host gene in chronic lymphocytic leukemia - Vargova, Karin; Curik, Nikola; Burda, Pavel; Basova, Petra; Kulvait, Vojtech; Pospisil, Vit; Savvulidi, Filipp; Kokavec, Juraj; Necas, Emanuel; Berkova, Adela; Obrtlikova, Petra; Karban, Josef; et al. (Blood, 2011)
Elevated levels of microRNA miR-155 represent a candidate pathogenic factor in chronic B-lymphocytic leukemia (B-CLL). In this study, we present evidence that MYB (v-myb myeloblastosis viral oncogene homolog) is overexpressed in a subset of B-CLL patients. MYB physically associates with the promoter of miR-155 host gene (MIR155HG, also known as BIC, B-cell integration cluster) and stimulates its transcription. This coincides with the hypermethylated histone H3K4 residue and spread hyperacetylation of H3K9 at MIR155HG promoter. Our data provide evidence of oncogenic activities of MYB in B-CLL that include its stimulatory role in MIR155HG transcription.
Keywords: onkogenní proteiny v-myb; Protein Binding; transfekce; Gene Expression Regulation, Leukemic; MicroRNAs; Cluster Analysis; mikročipová analýza; Transfection; Transcription, Genetic; mikro RNA; shluková analýza; promotorové oblasti (genetika); regulace genové exprese u leukemie; stanovení celkové genové exprese; Oncogene Proteins v-myb; chromatin; HeLa buňky; Gene Expression Profiling; genetická transkripce; Chromatin; vazba proteinů; Leukemia, Lymphocytic, Chronic, B-Cell; lidé; HeLa Cells; Humans; Promoter Regions, Genetic; nádorové buňky kultivované; Microarray Analysis; Tumor Cells, Cultured; chronická lymfatická leukemie